The impact of climate change on mental health of children and adolescents - Bolek, Monika; Dobrzeniecki, Krzysztof; Błaszczyszyn, Katarzyna; Hopej, Natalia; Muc, Katarzyna; Turek, Kacper (Quality in Sport, 2024)
Climate change can affect the mental health of children and adolescents. This age group is considered particularly vulnerable to this impact because they are in a period of cognitive and emotional development, during which they are still developing their coping skills. Children and teenagers with pre-existing mental health disorders, such as depression or anxiety, are especially at risk. It is important for parents, medical personnel, and others working with children and adolescents to have the necessary knowledge to help them cope with these challenges. This publication aims to present the current state of knowledge regarding the impact of climate change on the mental health of children and adolescents. Both the direct and indirect effects of these changes will be analyzed, along with strategies for coping with them. By understanding the potential risks, it is possible to develop effective psychological support strategies to minimize the negative impact of climate change on children and adolescents.